2023
DOI: 10.1039/d2nr05212a
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic hot carrier injection from single gold nanoparticles into topological insulator Bi2Se3 nanoribbons

Abstract: Plasmonic gold nanoparticles injecting hot carriers into the topological insulator (TI) interface of Bi2Se3 nanoribbons are studied by resonant Raman spectroscopy. We resolve the impact of individual gold particles with...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…The Raman tensors in Bi 2 Se 3 and the atomic displacements of the Raman‐active modes are well known. [ 32 ] The commonly grown morphologies of Bi 2 Se 3 G1D nanostructures are nanowires (NWs) and nanoribbons (NRs) as shown in Figure 1a,b. We earlier mentioned the observation of AB oscillations originating from the surface state of G1D TI.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Raman tensors in Bi 2 Se 3 and the atomic displacements of the Raman‐active modes are well known. [ 32 ] The commonly grown morphologies of Bi 2 Se 3 G1D nanostructures are nanowires (NWs) and nanoribbons (NRs) as shown in Figure 1a,b. We earlier mentioned the observation of AB oscillations originating from the surface state of G1D TI.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed information on the synthesis and characterization of the AuNPs has been reported previously. [32,51] Exemplary SEM and TEM images of the studied nanostructures are shown in the Supporting Information. A custom-made piezo-controlled micro-Raman setup was used (see Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmonic hot electrons can overcome or tunnel through energy barriers, allowing them to transfer to nearby objects. Plasmonic metal nanostructures are therefore promising candidates for plasmonic catalysis and photovoltaics. When metal nanoantennas come into contact with semiconductive materials such as silicon (Si) or titanium dioxide (TiO 2 ), a Schottky barrier is usually formed depending on the materials’ work functions. When excited by light, LSPR-induced hot electrons can have enough energy to pass this barrier and be injected from the metal to the semiconductor, , generating a photocurrent known as light harvesting. , Theoretical studies have shown that the photoemission efficiency of LSPR-induced hot electrons through a Schottky barrier of approximately 0.9 eV is generally limited to about 8% .…”
mentioning
confidence: 99%